2016
DOI: 10.1097/qai.0000000000001030
|View full text |Cite
|
Sign up to set email alerts
|

War-Related Abduction and History of Incarceration Linked to High Burden of HIV Among Female Sex Workers in Conflict-Affected Northern Uganda

Abstract: This study documented a high rate of undiagnosed HIV infections and associations between war-related human rights violations, incarceration, and a heavy HIV burden among SWs in conflict-affected Northern Uganda. These findings highlight the serious harms of conflict and criminalization of marginalized women in sub-Saharan African contexts. SW-led interventions that address conflict experiences and policy shifts to promote a rights-based approach to HIV prevention and care remain critically needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 47 publications
2
30
0
Order By: Relevance
“…Women who have a history of incarceration may be further marginalized and have reduced access to reproductive health services. Incarceration is hypothesized to be associated with HIV acquisition [2] , [13] . Pathways that lead from incarceration to increased HIV acquisition may be similar to those for pregnancy outcomes, and include marginalization and reduced access to healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…Women who have a history of incarceration may be further marginalized and have reduced access to reproductive health services. Incarceration is hypothesized to be associated with HIV acquisition [2] , [13] . Pathways that lead from incarceration to increased HIV acquisition may be similar to those for pregnancy outcomes, and include marginalization and reduced access to healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…2 Similarly, knowledge of status has been reported to be low in other regions of Sub-Saharan Africa among FSWs. 3,4 Interventions to improve HIV testing coverage for FSWs are warranted, the development of such interventions must include an understanding of existing barriers and facilitators to HIV testing from the perspective of this vulnerable community.…”
Section: Introductionmentioning
confidence: 99%
“…The economic, social and political instability of conflict and post-conflict environments, including social and physical displacement, loss of traditional economic options, cultural upheaval, family separation and increased women-headed households, often result in conditions that facilitate significant engagement in sex work as a source of income, particularly for women. Further, armed conflict and the highly policed and militarized environment characteristic of post conflict have been linked to widespread gender-based violence (including rape as a weapon of war; forced abductions), rights violations of women [ 3 , 11 17 ], and reduced access to, or the interruption of, HIV and sexual and reproductive health (SRH) programmes [ 4 , 18 21 ]. For example, previous research has shown that within conflict settings, the interruption of condom distribution, disruption of HIV diagnostic services, and shortages of HIV antiretroviral therapy (ART) may drastically impede diagnosis and care [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent global review identified a critical need for further studies examining structural HIV/STI risks or access to care for sex workers in the highest-HIV burden countries [ 9 ], to inform the design, adaptation and implementation of effective HIV/STI programmes, particularly needed within conflict-affected settings of sub-Saharan Africa. While sex workers are often highly marginalized even in non-conflict settings, in conflict-affected environments they may face elevated social and structural risks and barriers to care, including abuses of human rights by military and police, gender-based inequities, widespread violence, discrimination and stigma, social and physical isolation, breakdowns in health service delivery systems, and other structural risks that often accompany or follow a crisis [ 11 , 14 , 26 , 28 , 29 ]. Despite this, little is known about conflict-affected sex workers’ vulnerability to HIV/STIs or access to HIV and SRH services, or their social and structural drivers within conflict-affected settings.…”
Section: Introductionmentioning
confidence: 99%